Proceedings of the 34th International Cosmic Ray Conference — PoS(ICRC2015) 2016
DOI: 10.22323/1.236.0623
|View full text |Cite
|
Sign up to set email alerts
|

JEM-EUSO Science

Abstract: The Extreme Universe Space Observatory (EUSO) to be accommodated in the Japanese Experiment Module (JEM) of the International Space Station (ISS), JEM-EUSO, is designed to discover the origin of ultrahigh energy cosmic rays by observing extremely energetic extensive airshowers from space. The JEM-EUSO design is based on a wide field of view (60 •) refractor with an ultrafast 0.3M pixel UV camera that records the extensive airshower fluorescence and backscattered cherenkov. The main science goal of JEM-EUSO is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…It was demonstrated that if the detected luminosity of the hotspot is attributed to a physical effect and not a statistical fluctuation, the KLYPVE and JEM-EUSO experiments would need to collect approximately 300 events with energies above 57 EeV over the whole celestial sphere in order to detect the hotspot at the 5σ confidence level with 68% probability. It was estimated by Olinto et al (2015) that with the annual exposure ∼ 5 × 10 4 km 2 sr above ∼ 60 EeV, JEM-EUSO will collect 429 events/yr, or about 2,145 events in 5 years. KLYPVE will have the annual exposure ∼ 1.2 × 10 4 km 2 sr above 50 EeV (Panasyuk et al 2015;Sakaki et al 2015) and thus will be able to detect more than 100 events every year of operation, and more than 600 events during its planned lifetime.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…It was demonstrated that if the detected luminosity of the hotspot is attributed to a physical effect and not a statistical fluctuation, the KLYPVE and JEM-EUSO experiments would need to collect approximately 300 events with energies above 57 EeV over the whole celestial sphere in order to detect the hotspot at the 5σ confidence level with 68% probability. It was estimated by Olinto et al (2015) that with the annual exposure ∼ 5 × 10 4 km 2 sr above ∼ 60 EeV, JEM-EUSO will collect 429 events/yr, or about 2,145 events in 5 years. KLYPVE will have the annual exposure ∼ 1.2 × 10 4 km 2 sr above 50 EeV (Panasyuk et al 2015;Sakaki et al 2015) and thus will be able to detect more than 100 events every year of operation, and more than 600 events during its planned lifetime.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…JEM-EUSO is designed to observe ultra high-energy cosmic rays (UHECRs) by looking downward to the Earth's atmosphere from the ISS, observing the UV fluorescence light of UHECR-induced Extensive Air Showers (EAS). This conference includes a number of detailed articles on JEM-EUSO, notably its status [1], the science case [2]; for an overview of the JEM-EUSO instruments see [3].…”
Section: Contextmentioning
confidence: 99%
“…At such energies, the flux is as low as 1 particle/km 2 /century and the effective area that can be observed by a detector is a key feature. The JEM-EUSO Collaboration aims to detect the UV light produced by EECR-induced atmospheric showers from the vantage point of low Earth orbit, thereby largely increasing the effective detector volume [1,2]. In order to lay the groundwork for such unprecedented observations, the JEM-EUSO collaboration has successfully initiated several pathfinder experiments.…”
Section: Introductionmentioning
confidence: 99%